Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

6. If [tex]\cot \theta=\frac{17}{4}[/tex], then find [tex]\frac{(2+2 \sin \theta)(1-\sin \theta)}{(1+\cos \theta)(2-2 \cos \theta)}[/tex].

Sagot :

Certainly! Let's break down the problem step by step to solve the expression given [tex]\(\cot \theta = \frac{17}{4}\)[/tex].

1. Given Information:
[tex]\[ \cot \theta = \frac{17}{4} \][/tex]
Recall that:
[tex]\[ \cot \theta = \frac{\cos \theta}{\sin \theta} \][/tex]

2. Determine [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex]:

First, we need to work out [tex]\(\sin \theta\)[/tex] and [tex]\(\cos \theta\)[/tex].

We know that:
[tex]\[ \cot \theta = \frac{\cos \theta}{\sin \theta} = \frac{17}{4} \][/tex]
Therefore,
[tex]\[ \cos \theta = 17k \][/tex]
[tex]\[ \sin \theta = 4k \][/tex]

To find [tex]\(k\)[/tex], we use the Pythagorean identity:
[tex]\[ \cos^2 \theta + \sin^2 \theta = 1 \][/tex]

Substitute [tex]\(\cos \theta = 17k\)[/tex] and [tex]\(\sin \theta = 4k\)[/tex]:
[tex]\[ (17k)^2 + (4k)^2 = 1 \][/tex]
[tex]\[ 289k^2 + 16k^2 = 1 \][/tex]
[tex]\[ 305k^2 = 1 \][/tex]
[tex]\[ k^2 = \frac{1}{305} \][/tex]
[tex]\[ k = \frac{1}{\sqrt{305}} \][/tex]

So,
[tex]\[ \sin \theta = 4k = \frac{4}{\sqrt{305}} \approx 0.229 \][/tex]
[tex]\[ \cos \theta = 17k = \frac{17}{\sqrt{305}} \approx 0.973 \][/tex]

3. Calculate the numerator: [tex]\((2 + 2 \sin \theta)(1 - \sin \theta)\)[/tex]:
[tex]\[ 2 + 2 \sin \theta = 2 + 2 \times 0.229 \approx 2.458 \][/tex]
[tex]\[ 1 - \sin \theta = 1 - 0.229 = 0.771 \][/tex]
[tex]\[ \text{Numerator:} (2 + 2 \sin \theta)(1 - \sin \theta) \approx 2.458 \times 0.771 \approx 1.895 \][/tex]

4. Calculate the denominator: [tex]\((1 + \cos \theta)(2 - 2 \cos \theta)\)[/tex]:
[tex]\[ 1 + \cos \theta = 1 + 0.973 \approx 1.973 \][/tex]
[tex]\[ 2 - 2 \cos \theta = 2 - 2 \times 0.973 \approx 2 - 1.946 = 0.054 \][/tex]
[tex]\[ \text{Denominator:} (1 + \cos \theta)(2 - 2 \cos \theta) \approx 1.973 \times 0.054 \approx 0.105 \][/tex]

5. Evaluate the expression:
[tex]\[ \frac{(2 + 2 \sin \theta)(1 - \sin \theta)}{(1 + \cos \theta)(2 - 2 \cos \theta)} \approx \frac{1.895}{0.105} \approx 18.062 \][/tex]

Thus, the value of the expression is:
[tex]\[ \frac{(2+2 \sin \theta)(1-\sin \theta)}{(1+\cos \theta)(2-2 \cos \theta)} \approx 18.062 \][/tex]